The MR appearance of CSF pulsations in the spinal canal. - Sherman, J L; Citrin, C M; Gangarosa, R E; Bowen, B J (American Journal of Neuroradiology, 1986)
We investigated the MR appearance and incidence of low-signal areas within the CSF of the spinal canal. Nonuniform areas of decreased signal intensity in intracranial CSF have been named the CSF flow-void sign (CFVS) and appear to be due to spin dephasing secondary to pulsatile CSF motion. Similar areas are seen in the spinal canal. The MR scans of 50 randomly selected patients, constituting a total of 63 spinal studies, were reviewed. There were 27 cervical, 16 thoracic, and 20 lumbar spine examinations. All patients were studied using T2-weighted and T1-weighted spin-echo pulse sequences. T2-weighted images were done with sufficiently long TE and TR to cause the CSF to appear hyperintense compared with brain and spinal cord tissue. Two patients with enlarged spinal canals and two patients with syringohydromyelia were also included to illustrate the appearance of prominent CSF pulsations. The CFVS was identified on T2-weighted scans in the cervical spinal canal in nine patients (33%), in the thoracic spinal canal in one patient (6%), and possibly in the lumbar spinal canal in two patients (10%). The CFVS was prominent in two patients with enlarged CSF spaces and was also seen in the intramedullary cavity of the patients with syringohydromyelia. The CFVS could obscure small dural lesions and, in some instances, simulate enlarged vessels. Recognition of the spinal CFVS is important to avoid the incorrect diagnosis of intraspinal lesions.